2017
DOI: 10.1002/2017jb014603
|View full text |Cite
|
Sign up to set email alerts
|

GPS Recovery of Daily Hydrologic and Atmospheric Mass Variation: A Methodology and Results From the Australian Continent

Abstract: We present a methodology to invert a regional set of vertical displacement data from Global Positioning System (GPS) to determine the surface mass redistribution. It is assumed that GPS deformation is a result of the Earth's elastic response to the surface mass load of hydrology, atmosphere, and/or ocean. We develop an algorithm to estimate the spectral information of displacements from “regional” GPS data through regional spherical (Slepian) basis functions and apply the load Love numbers to estimate the mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…A few recent hydrogeodetic studies have inverted GNSS displacements to estimate high‐frequency TWS changes at timescales as short as 1 day (Han & Razeghi, 2017; Jiang et al., 2021; Milliner et al., 2018; Zhan et al., 2021). For instance, Milliner et al.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A few recent hydrogeodetic studies have inverted GNSS displacements to estimate high‐frequency TWS changes at timescales as short as 1 day (Han & Razeghi, 2017; Jiang et al., 2021; Milliner et al., 2018; Zhan et al., 2021). For instance, Milliner et al.…”
Section: Applicationsmentioning
confidence: 99%
“…A few recent hydrogeodetic studies have inverted GNSS displacements to estimate high-frequency TWS changes at timescales as short as 1 day ( Han & Razeghi, 2017;Jiang et al, 2021;Milliner et al, 2018;Zhan et al, 2021 ). For instance, Milliner et al ( 2018 ) quantified flood volumes as daily changes in water storage during and following Hurricane Harvey and tracked the movement of stormwaters using 198 GNSS stations in the Southern Texas and Louisiana region, USA.…”
Section: Subseasonal and Storm Event-scale Storagementioning
confidence: 99%
“…For the SBF method, Han and Razeghi (2017) first introduced the SBF into the inversion of surface mass changes using GNSS vertical displacements in the Australian continent, and the results demonstrated that the GNSS‐inverted surface mass changes were in good agreement with the GRACE and hydrologic model estimates. Based on the research of Han and Razeghi (2017), Jiang, Hsu, Yuan, Cheng, et al. (2021), and Jiang et al.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach to the study of TWS is to employ ground‐based Global Positioning System (GPS) observations of surface displacement (most notably vertical displacement) based on the elastic response of the Earth’s surface to mass redistribution (Argus et al., 2017; Borsa et al., 2014; van Dam et al., 2001). Through a comparison of vertical displacements derived from hydrologic models, GRACE, and ground‐based GPS, the capability of ground‐based GPS observations to infer TWS changes has been demonstrated in regions across the globe such as in the Himalayas (Chanard et al., 2014; Fu & Freymueller, 2012; Zhang et al., 2018), the western United States (Knappe et al., 2019; Tan et al., 2016; Wahr et al., 2013; Yin et al., 2020), the North China Plain (Wang et al., 2017), and Australia (Han & Razeghi, 2017). A number of studies have attempted to use ground‐based GPS observations of vertical displacement to estimate TWS changes at both regional (Argus et al., 2014, 2017) and continental (Ferreira et al., 2019) scales, and GPS‐based TWS anomalies have been successfully applied to study the impact of drought (Borsa et al., 2014) and hurricanes (Milliner et al., 2018) on the terrestrial water cycle.…”
Section: Introductionmentioning
confidence: 99%